Evolution of intracranial atherosclerotic disease under modern medical therapy. Issue 3 (29th January 2015) - Leung, Thomas W.; Wang, Lily; Soo, Yannie O. Y.; Ip, Vincent H. L.; Chan, Anne Y. Y.; Au, Lisa W. C.; Fan, Florence S. Y.; Lau, Alex Y. L.; Leung, Howan; Abrigo, Jill; Wong, Adrian; Mok, Vincent C. T.; et al.
<x xml:space="preserve">Abstract</x> Objective Understanding how symptomatic intracranial atherosclerotic disease (ICAD) evolves with current medical therapy may inform secondary stroke prevention. Methods In a prospective academic‐initiated study, we recruited 50 patients (mean age = 63.4 ± 9.0 years) with acute strokes attributed to high‐grade (≥70%) intracranial atherosclerotic stenosis for 3‐dimensional rotational angiograms before and after intensive medical therapy for 12 months. Treatment targets included low‐density lipoprotein ≤ 70mg/dl, glycosylated hemoglobin (HbA1c) ≤ 6.5%, and systolic blood pressure ≤ 140 mmHg. We analyzed infarct topography and monitored microembolic signal in recurrent strokes. The reference group was a published cohort of 143 ICAD patients. Results Overall, the stenoses regressed from 79% at baseline (interquartile range [IQR] = 71–87%) to 63% (IQR = 54–74%) in 1 year (p < 0.001). Specifically, the qualifying lesions (n = 49) regressed (stenosis reduced >10%) in 24 patients (49%), remained quiescent (stenosis same or ±10%) in 21 patients (43%), and progressed (stenosis increased >10%) in 4 patients (8%). There was no difference in intensity of risk factor control between groups of diverging clinical or angiographic outcomes. Higher HbA1c at baseline predicted plaque regression at 1 year (odds ratio = 4.4, 95% confidence interval = 1.4–14.5, p = 0.006). Among the 6 patients with recurrent strokes pertaining to the qualifying stenosis, 5 patients had solitary or rosarylike acute infarcts along the internal or anterior border zones, and 2 patients showed microembolic signals in transcranial Doppler ultrasound. Interpretation A majority of symptomatic high‐grade intracranial plaques had regressed or remained quiescent by 12 months under intensive medical therapy. Artery‐to‐artery thromboembolism with impaired washout at border zones was a common mechanism in stroke recurrence. Ann Neurol 2015;77:478–486